Social Networks and Mobile Applications Use in Young Patients With Kidney Disease - Haddad, Raymond N.; Mourani, Chebl C. (Frontiers in Pediatrics, 2019)
Objective: To evaluate the use and benefits of social networking sites (SNS) and mobile applications (MA) in young patients with kidney disease (KD). Background: Pediatric KD is prevalent. The Internet is increasingly being used to communicate rapid healthcare information to children about acute and chronic diseases with greater medical care satisfaction. There is lack of data on social media (SM) utility in pediatric KD. Materials and Methods: A descriptive, observational and cross-sectional study was conducted on a national level. Data were collected from 4 different centers through a reviewed questionnaire. Results: 83.9% of the 428 participants were Lebanese. The average age was 11.4 years (± 7.1). 69.9% had chronic KD out of which 17.4% had undergone a kidney transplant while 9% were on dialysis. 69.6% of our participants affirmed the need of SM for the health of the sick child while only 9.8% are participating in a scientific forum and 4.7% used SM to find a potential organ donor. Some study variables were statistically associated with the participants’ age, nationality and stage of KD. Conclusions: SM are important for the support and management of pediatric KD. We believe that SNS and MA will play a leading role in the lives of our patients in the future and will push the physician to play a central role in the evolution of communication networks. To identify the potential role and the efficacy of SM in enhancing communication between patients and health professionals, further stratified studies are needed.